A culture of control?. Issue 3 (3rd February 2019) - Hawick, Lorraine; Thomson, Alan; Cleland, Jennifer
Abstract : The authors respond to Zeeman et al's analysis of how students use their time, suggesting it would be valuable to shift from quantitative to qualitative measures.